COMPARATIVE AND APPLIED LINGUISTICS: GLOBAL APPROACHES - To’lqinova Mushtariybegim Erkinjon qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Comparative and Applied Linguistics is an important field of study that explores how languages are analyzed, compared, and used in practical contexts across different societies. It helps researchers identify similarities and differences among languages, including grammar, vocabulary, pronunciation, and communication styles. By examining these features, scholars can develop more effective methods for language teaching and learning. In today’s globalized world, comparative and applied linguistics pays special attention to multilingualism, cultural diversity, and cross-cultural communication. It studies how people use multiple languages in everyday life and how educational systems can respond to diverse linguistic needs. This discipline also investigates modern teaching strategies, second language acquisition, and the role of technology in language education. Furthermore, applied linguistics provides solutions to real-world challenges such as translation, interpreting, language planning, and language policy development. It supports governments, schools, and organizations in creating fair and efficient communication systems. Comparative studies also help preserve endangered languages and promote respect for linguistic diversity worldwide. Through its global approaches, this field contributes to stronger international understanding and cooperation. Overall, Comparative and Applied Linguistics plays a significant role in improving language education, solving communication problems, and building connections between people from different cultural and linguistic backgrounds in an increasingly interconnected world today.